ESOLS, SOFT POWER, AND NOMADISM: THAI CREATOR CULTURE IN THE SHADOW OF PLATFORM NATIONALISM - Craig, David; Yutthaworakool, Saittawut; Salathong, Jessada (AoIR Selected Papers of Internet Research, 2026)
This research maps the distinctiveness and evolution of Thailand’s (or Thai) creator culture, which refers to the rapidly-emerging platform-based cultural economies vitally distinguished by the practices of social media entrepreneurs, whether referred to as creators or influencers, KOLS or wanghong, YouTubers or TikTokers, game players or mukbangers, and/or vloggers or streamers. This work is framed by the concept of platform nationalism, the multilateral power relations engaged by corporations and governments to engage platform and social media users, communities, and entrepreneurs around nationalistic causes and movements. The preliminary results reveals a vibrant and rapidly-evolving creator economy, paradoxically promoted by government incentives around encouraging soft power abroad, if limited by platform and industry practices that inhibit the growth of sustainable creator businesses. More precariously, Thai creator culture is increasingly distinguished by the seller creator model operating solely off of Chinese owned, or funded, e-commerce platforms.